Pengaruh Kualitas Produk Dan Harga Terhadap Keputusan Pembelian Rozs Perfumery - Nuslih Jamiat; Riffa Naufal Musyaffa (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The development of perfume in Indonesia is growing very rapidly. Making sales competition between perfume companies higher and making it difficult for companies to compete. One of them Rozs Perfumery must have the maximum ability to produce improvements in product quality and affordable price quotes to attract purchasing decisions made by consumers. With this, it is known that product quality and price at Rozs Perfumery still have many shortcomings. This study is intended to examine the effect of product quality and price on purchasing decisions on Rozs Perfumery products. The research method used is descriptive quantitative with a questionnaire in collecting data on 100 respondents. A number of analytical procedures used are validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, correlation and determination coefficient analysis, to research hypotheses, using SPSS software. As the research findings, the regression equation Y = 12.035, X1 = - 0.297, X2 = 1.075 was obtained. This study found that the effect of product quality and price on purchasing decisions for Rozs Perfume Perfumery was 88.7%, and the rest was influenced by other factors not included in the study. It is known that product quality and price have a significant positive effect on purchasing decisions for Rozs Perfumery perfume.